2006
DOI: 10.1101/gr.5320706
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous carriers of Nijmegen Breakage Syndrome have a distinct gene expression phenotype

Abstract: Autosomal recessive diseases are those that require mutations in both alleles to exhibit the disorder. Although most recessive conditions are rare, heterozygous carriers of recessive mutations are quite common. In this study, we show that carriers of Nijmegen Breakage Syndrome (NBS) have a distinct gene expression phenotype that differs from that of noncarriers and also from that of carriers of a similar syndrome, Ataxia Telangiectasia (AT). We found 520 genes whose expression levels differ significantly (P Յ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…We next sought insight into mechanisms of differential responsiveness to RSV in LCLs by infecting 42 HapMap CEU LCLs to leverage genetic and genomic information available for the lines (3135). As above, we found significant interindividual variation in viral RSV‐G expression following infection with RSV ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next sought insight into mechanisms of differential responsiveness to RSV in LCLs by infecting 42 HapMap CEU LCLs to leverage genetic and genomic information available for the lines (3135). As above, we found significant interindividual variation in viral RSV‐G expression following infection with RSV ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…37; and GSE11582, ref. 31) from the U.S. National Center for Biotechnology Information (NCBI; Bethesda, MD, USA) Gene Expression Omnibus (GEO) database (http://www.ncbi.nlm.nih.gov/geo/) for the LCLs. We then used a 3‐step approach: first, we performed linear regression of log 2 ‐transformed RSV‐G expression on log 2 ‐transformed gene expression values of every detectable gene; second, we compared the average gene expression levels for the 5 individuals with the highest RSV‐G expression against that for the 5 individuals with the lowest RSV‐G expression using t test (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This anomalous chromosomal behaviour still persists during the first mitotic divisions[65] and is paralleled by diminished mRNA levels of several checkpoint proteins and also of cohesin (reviewed in [66]). Carriers of the NBN c.657del5 mutation have a distinct gene expression phenotype with about the same number of genes up- and down regulated [67]. Moreover, based upon SDS-PAGE and mass spectrometry, it was shown that the two truncated proteins, p26 and p70, synthesized by carriers of the mutation, bind to proteins that do not interact with full-length nibrin [68].…”
Section: Discussionmentioning
confidence: 99%
“…(17) Heterozygous mutations in the NBS1 gene have been described in various groups of cancer patients, for example, patients with acute lymphoblastic leukemia (ALL), (18,19) non-Hodgkin's lymphoma (NHL), (20) and in cancer cell lines.…”
mentioning
confidence: 99%
“…(14) Recent findings show that besides spontaneous chromosome instability, (15,16) cells from NBS1 gene mutation carriers are characterized by a distinct gene expression phenotype. (17) Heterozygous mutations in the NBS1 gene have been described in various groups of cancer patients, for example, patients with acute lymphoblastic leukemia (ALL), (18,19) non-Hodgkin's lymphoma (NHL), (20) and in cancer cell lines. (21) Recent studies strongly suggest that heterozygous 657del5 mutation carriers have an elevated risk of malignant tumor development, especially of melanoma, (22,23) colon and rectum cancer, (23) prostate cancer, (24) ovarian cancer, (25) breast cancer (26,27) and NHL.…”
mentioning
confidence: 99%